2010
DOI: 10.1002/bdra.20732
|View full text |Cite
|
Sign up to set email alerts
|

Maternal polymorphisms in folic acid metabolic genes are associated with nonsyndromic cleft lip and/or palate in the Brazilian population

Abstract: The findings of the present study suggested that genetic variants of folic acid metabolic genes may modulate maternal susceptibility for having an offspring with NSCL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 46 publications
2
41
0
2
Order By: Relevance
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence in support of this idea has recently been published. 15 As such, some genetic effects on disease risk can operate via a mechanism of maternal/fetal interaction. Previous candidate gene studies have suggested evidence for PofO effects in CL/P providing a strong rationale for performing comprehensive analysis to identify unconventional modes of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the developmental mechanisms underlying NSCL/P, it is essential to review a large and varied field of research 14 . The environmental risk factors for NSCL/P include maternal use of medications such as antiepileptic agents or corticosteroids, smoking and alcohol consumption during pregnancy 15 , intrapartum interval 10 , parity 16 , folic acid deficiencies 17 and maternal and paternal age 5 . However, there is no consensus on the association of parental age and NSCL/P 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of a second polymorphism within the MTHFR coding region, 1298A>C in NTD susceptibility has been controversial (Koch et al, 1998;van der Put et al, 1998). Several other polymorphisms in the MTHFR gene have been reported to influence the homocysteine levels and thus likely associated with NTD and other related disorders such as cleft lip and palate (Botto and Yang, 2000;Bufalino et al, 2010). Transcobalamin (TCN2) is another gene of interest based on findings of low vitamin B 12 and holo-TC concentrations in women with NTD-affected fetuses.…”
Section: Introductionmentioning
confidence: 99%